The relationship between individual behaviour (Mars Model) and job performances among non-executives staff at LONGi, Kuching / Vanessa Renyold - Renyold, Vanessa (2017)
The purpose of the correlational research was to investigate the study of the relationship between Individual Behaviours (MARS Model) and Job Performance by adapting Model of Organization Behaviours, Source: Mc Shane (2010). A study conducted by McShan and Glinow (2010), the acronym MARS stands for motivation, ability, role perceptions and situational factors. Independent variables are divided into three which is motivation, ability and role perception. Meanwhile for dependent variables is job performance. The aim of this study is to find the relationship between motivation, ability, role perception and job performance among non-executive staff in LONGi, Kuching. Convenience Sampling was used in this study where questionnaire were distributed to 120 respondents to the non-executive staff and returned only 92 respondents. The respondents came from various departments at LONGI, Sarawak and the data was analysed using IBM Statistic Packages for Science Social version 2.0. The correlation analysis revealed that motivation, ability and role perception have a significant relationship towards job performance among non-executive staff in LONGi, Kuching. Not only that, the results also showed that all the three independent variables have positive relationship with job performance. Motivation has medium relationship with job performance, meanwhile for ability and role perception both have large relationship with job performance. The findings of this study provide a reference to the management in terms of employee’s job performance. It is recommended for future researchers to select larger sample of respondents to obtain more information about what really impact job performance and to determine the importance of the factors towards job performance.